[The factory, 1957] - Carter, Jeff, 1928-2010. (1957)
Caption accompanying the photograph: "The factory -- Batlow, NSW -- Ideally, the bush eycalpytus {i.e. eucalyptus} still was located close by a source of water such as this tiny creek. Oil and water vapour condensed in an underwater pipe leading to a collection drum where the oil floating on the water was skimmed off".
Condition: good.
Title devised by cataloguer based on information from acquisition file number 204/04/00122.
Also available online
Keywords: Simpson family; Simpson, Sharkey -- Portraits; Eucalyptus oil industry -- New South Wales -- Batlow -- Photographs; Distilling industries -- New South Wales -- Batlow -- Photographs; Batlow (N.S.W.) -- Photographs; Distillers